Influenza H2 haemagglutinin activates B cells via a MyD88-dependent pathway. - Marshall-Clarke, S; Tasker, L; Buchatska, O; Downes, J; Pennock, J; Wharton, S; Borrow, P; Wiseman, D (2006)
Influenza viruses are serious respiratory pathogens, responsible for half a million deaths each year. The viral surface haemagglutinin (HA) protein has been shown to be an important determinant of viral pathogenicity. HA is the virion attachment and fusion protein, and the major target for neutralizing antibodies; however, it is also involved in triggering innate responses that may have an important impact on the disease course. We have examined the role of the toll-like receptor (TLR) family in innate responses to influenza virus and influenza HA. TLR7 has recently been found to mediate recognition of influenza RNA. Here, we show for the first time that influenza HA of the H2 subtype induces innate responses in murine B lymphocytes via a MyD88-dependent pathway distinct from that involved in sensing viral RNA. We also show that inactivated influenza virus induces activation of human B cells. Our findings suggest that the molecule mediating these responses may be a novel member of the TLR family.